Studi Kelayakan Bisnis Kewirausahaan Makanan Beku pada UMKM Dumpling House di Semarang - Salim, Elizabeth Gina Mitayanny; Harianto, Eric (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2025)
The food sector is a fundamental human need that must be met to ensure well-being, as regulated by the Government Regulation of the Republic of Indonesia Number 17 of 2015. MSMEs in the food sector play a crucial role in Indonesia's economy by absorbing up to 97% of the workforce. Dumpling House, an MSME specializing in frozen food that prioritizes employees with disabilities, experienced a 30% decline in revenue in 2023. This study employs a quasi-qualitative method to analyze the feasibility of Dumpling House's management system from legal, market and marketing, technical and operational, managerial, and financial aspects to identify the causes of the decline in sales. The findings indicate that the company remains feasible for operation; however, the sales decline from 2022 to 2023 was due to suboptimal marketing strategies. Additionally, the legal, management and human resources, as well as technical and operational aspects, require updates to maintain business feasibility. This research is expected to provide insights for the development of MSME management systems and enhance the understanding of the importance of feasibility in ensuring business sustainability